Extension and Comparative Study of AUSM-Family Schemes for Compressible Multiphase Flow Simulations (Communications in Computational Physics, 2014)
Several recently developed AUSM-family numerical flux functions (SLAU,SLAU2, AUSM+-up2, and AUSMPW+) have been successfully extended to computecompressible multiphase flows, based on the stratified flow model concept, by following two previous works: one by M.-S. Liou, C.-H. Chang, L. Nguyen, and T.G.Theofanous [AIAA J. 46:2345-2356, 2008], in which AUSM+-up was used entirely, andthe other by C.-H. Chang, and M.-S. Liou [J. Comput. Phys. 225:840-873, 2007], inwhich the exact Riemann solver was combined into AUSM+-up at the phase interface. Through an extensive survey by comparing flux functions, the following arefound: (1) AUSM+-up with dissipation parameters of Kp and Ku equal to 0.5 or greater,AUSMPW+, SLAU2, AUSM+-up2, and SLAU can be used to solve benchmark problems, including a shock/water-droplet interaction; (2) SLAU shows oscillatory behaviors [though not as catastrophic as those of AUSM+ (a special case of AUSM+-up with Kp=Ku=0)] due to insufficient dissipation arising from its ideal-gas-based dissipationterm; and (3) when combined with the exact Riemann solver, AUSM+-up (Kp=Ku=1),SLAU2, and AUSMPW+ are applicable to more challenging problems with high pressure ratios.